Stosunki pracy w wielkopolskich majątkach ziemskich w okresie międzywojennym - Janicki , Tadeusz (Człowiek i Społeczeństwo, 2014)
In the period between the two world wars large landowners in the Wielkopolska region employed the largest number of hired labourers in the area. The main subject of this article is the professional and personal relations between land estate owners and the two main groups of hired workers (the economic administration staff and the farm workers). The labour relations in Wielkopolska’s land estates were based on a strictly observed hierarchy and division of duties. In interpersonal relations we may notice some patriarchal and technocratic elements. In the case of the former, they were mainly inspired by the landowners (or, in a wider sense, by the residents of the manor house), while the technocratic elements were contributed mainly by the administration staff. The labour relations on land estates were slowly evolving under the influence of legal regulations and were additionally shaped by the economic and cultural developments. The impact of this process on the actual organization of labour was rather limited. It was much more evident in the change of relations between people, which evolved mainly under the influence of the process of change in the consciousness of agricultural workers to replace traditional relations, based on patriarchal ones and manoralism or serfdom-based relations, into professional and contract-based labour relations. However, the trends to modernise the land estates during the 1920s, both in the sphere of technology and social relations, became impeded by the impact of the economic crisis of the 1930s which led again to further consolidation of the patriarchal employer-employee model of relations.